2021
DOI: 10.3389/fmats.2020.617199
|View full text |Cite
|
Sign up to set email alerts
|

Performance Investigation of a Solar Thermal Collector Based on Nanostructured Energy Materials

Abstract: The convective and conductive heat transfer between the solar collector and working fluids make photothermal performance limited, and result in a higher rate of heat loss from the surface of the conventional absorber to the surroundings. Direct absorption solar collectors (DASC) are a favorable alternative for their improved photothermal performance. In this study, a simulation based on the performance of a nanostructured solar collector has been carried out using TRNSYS. The connective and conductive heat tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Therefore, by controlling the loading concentration of the nanoparticles, and hence the internal structure of the nanofluid, up to 45% of the solar irradiance can potentially be absorbed and converted into electrical and thermal energy (figure 4(b)). It is feasible to consider that, through further refinement of the particle geometries, flow rate conditions, and the collector architecture, higher collector performances could potentially be achieved [13,14,25,31,49]. However, such investigations are outside the scope of this current work.…”
Section: Solar Energy Conversion Performance Of Pvt System With Ag Nanofluidsmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, by controlling the loading concentration of the nanoparticles, and hence the internal structure of the nanofluid, up to 45% of the solar irradiance can potentially be absorbed and converted into electrical and thermal energy (figure 4(b)). It is feasible to consider that, through further refinement of the particle geometries, flow rate conditions, and the collector architecture, higher collector performances could potentially be achieved [13,14,25,31,49]. However, such investigations are outside the scope of this current work.…”
Section: Solar Energy Conversion Performance Of Pvt System With Ag Nanofluidsmentioning
confidence: 97%
“…These issues can be tackled by exploiting the capability of nanoparticles to modulate light-matter interactions at the nanoscale. Thus, the thermal and/or optical properties of a base fluid (any conventional liquid) can be selectively augmented to increase its performance [24,25]. This can allow for conventional HTFs such as water to be repurposed for highperformance PVT applications through careful control and consideration of the nanoparticles size, shape, and distribution throughout the base fluid [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the output performance is reduced to 22 percent.After a continuous ten weeks of dust assertion on PV module, mass to volume ratio of dust on the surface from 0.01 g/m 2 at the beginning but it was gradually changed to 6 g/m 2 at the last day of this experimental study [55]. The transmission coefficient and energy conservation performance were reduced caused by dust assertion on the exterior upper layer of PV system [41,51,[56][57][58][59][60][61]. The rate of reduction in the output efficiency of a crystalline PV system is directly corresponding to quantity of dust assertion on the surface, is equal to 25% per micrometer.…”
Section: Introductionmentioning
confidence: 99%